Analysis of the association between SLCO1B1 genetic polymorphism (rs4149056) and lipid profile among statin users of HUSM, Kelantan - Yusri, Nur Farah Izzati (2022)
Statin is a medication that was proven to treat hyperlipidaemia effectively. Despite its well-known efficacy in statin users, the cases of its effectiveness have been reported. Single nucleotide polymorphism of rs4149056 in SLCO1B1 gene has been reported to alter the efficacy of statin. Until now there is no genetic association study among Malaysian population has been reported pertaining the influence of SNP on the efficacy of statin. Thus, the aim of this study is to investigate the association between SLCO1B1 rs4149056, patient’s demographic profiles and other clinical features among statin’s users from HUSM, Kelantan. Information regarding the demographic and clinical features of statin’s users obtained through examination of patient’s medical record. The extracted DNAs for this study were obtained from previous researcher. The genotyping of selected DNA sample of statin’s users was performed by using ARMS-PCR technique followed by gel electrophoresis. The results indicated that, there were no different in demographic profiles and clinical features between group 1 (those who achieved LDL-c level <2.60 mmol/L) and group 2 (those who achieved LDL-c level >2.60 mmol/L) except for concomitant drugs. The minor allele frequency (MAF) of the SNP value obtained was 0.23. However, there is no variables (age, race, gender, type of statin, concomitant drugs, supplement, genotype, physical activity, diet and smoking status) that are statistically significant associated with the achievement of LDL-c goal of <2.60 mmol/L. In conclusion, the SLCO1B1 rs41419056 polymorphism had no effect on lipid level changes in 72 hyperlipidaemic statin users.